Engineering Drawing - Jolhe, Dhananjay A. (New Delhi Tata McGraw Hill, 2009)
This book is meant for the Engineering Drawing course offered to the students of all engineering disciplines in their first year. An important highlight of this book is the inclusion of practical hints along with theory which would enable the students to make perfect drawings.
Keywords: Mechanical Engineering